2008
DOI: 10.1186/bcr2195
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 expression by breast-cancer-associated macrophages: IL-17 promotes invasiveness of breast cancer cell lines

Abstract: Introduction IL-17 plays an important role in autoimmunity, promoting autoimmunity, inflammation and invasion in multiple sclerosis, rheumatoid arthritis and type I diabetes. The role of IL-17 in cancer is unclear, however, as there are few studies examining IL-17 protein expression in cancer. We therefore examined IL-17 protein expression in human breast cancer and modelled its potential biological significance in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(178 citation statements)
references
References 47 publications
10
165
1
2
Order By: Relevance
“…Furthermore, invitro analysis showed that alveolar macrophages upregulated IL-17 expression via mast-cell-derived mediators (16). Moreover, IL-17 expression has been detected in breast tumor tissue within the scattered tumor-associated inflammatory infiltrate identified as macrophages (20). In our study, up to 35% of IL-17A-producing cells were CD68 + , suggesting that in RA this lineage can also contribute to IL-17A production.…”
Section: Resultssupporting
confidence: 55%
“…Furthermore, invitro analysis showed that alveolar macrophages upregulated IL-17 expression via mast-cell-derived mediators (16). Moreover, IL-17 expression has been detected in breast tumor tissue within the scattered tumor-associated inflammatory infiltrate identified as macrophages (20). In our study, up to 35% of IL-17A-producing cells were CD68 + , suggesting that in RA this lineage can also contribute to IL-17A production.…”
Section: Resultssupporting
confidence: 55%
“…23 We found significant increased level of IL-17 in adjacent tissue of malignant tumor compared to the surrounding tissue of benign tumor. Our results were consistent with those of Zhu et al 24 The results of current study elucidated no significant difference between IFN-γ level in malignant tumor tissue and benign tumor tissue. These results were in agreement with the findings of Rosen et al, which demonstrated that, contrary to IL-4, there was no significant difference between the secretion level of Th1 cytokines such as IFN-γ in concanavalin A-(Con A) and P43 antigen-treated T cells of malignant breast cancer patients and benign tumor patients as well as serum level of IFN-γ between breast cancer patients and women with suspected breast cancer who had negative pathological features of breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…From patients' material, it is Zhu et al [6] who initially reported the expression of IL-17 in human BC microenvironment. Though molecular type of tumour was not specified, most of the patients had grade III lesions.…”
Section: Review Sectionmentioning
confidence: 99%